Keterkaitan Employer Branding, Psychological Empowerment, dan Job Crafting dengan Kepuasan Kerja Karyawan di Era Digital - Dwi Kristanto; Hasan Ipmawan; Maruji Pakpahan; Aris wahyu Kuncoro (Pusat Riset dan Inovasi Nasional, 2026)
Employee job satisfaction plays a crucial role in increasing productivity and retention. Factors such as Employer Branding, Psychological Empowerment, and Job Crafting are believed to have a positive influence on job satisfaction. This study aims to examine the influence of these three factors on job satisfaction among non-production employees at PT Surya Toto Indonesia Tbk. This study used a survey method with questionnaires completed by 98 non-production employees selected from a total sample. Data were analyzed using SPSS to test validity, reliability, and the interrelationships between the variables. The results showed that Employer Branding, Psychological Empowerment, and Job Crafting have a positive and significant influence on employee job satisfaction. These findings suggest that companies that have a positive image, empower employees, and provide freedom to customize their work can increase job satisfaction.